Methodological aspects of organic production and balanced nature management - О. F. SТАSІV; R. А. NАКОNЕCНNYI; А. D. КОPYТКО (Передгірне та гірське землеробство і тваринництво, 2022)
The role of the Ukrainian school of physical economy as one of the important methodological aspects of building a system of organic production and sustainable use of nature in Ukraine and the world is highlighted. The authors draw attention to the importance of the close connection of specialized (scientific) knowledge with philosophical knowledge as an important basis for the harmonious coexistence of man and nature in modern conditions and in the future. It is emphasized that the content of this science, its focus are the sharpest weapons of man in the struggle for survival, for better adaptation to environmental conditions. The range of problems that become obstacles to the realization of the goals and objectives of organic production and sustainable use of nature in modern Ukraine is outlined. The problem of interaction of special sciences with philosophy, saturation of concrete-scientific knowledge with provisions in which certain philosophical ideas are reflected in a certain way is covered. The article substantiates the role of the philosophy of organic production and sustainable use of nature in changing the attitude of man and society not only to nature but also their own physical, intellectual and moral and spiritual health from consuming and contemptuous to harmonious, where man realizes himself an integral part of space processes.